Hotel restaurants’ challenges and critical success factors in Klang Valley, Malaysia: the inseparable roles of support centers and revenue streams - Lee, Sanghyeop; Lee, Kai Sean; Chua, Bee Lia; Han, Heesup (Routledge, 2019)
Hotel restaurants are of great importance in hotels, and the factors for this have so far been considerably understudied. This study investigated the challenges and critical success factors (CSFs) of restaurants owned and operated by five-star luxury hotels in Klang Valley, Malaysia. Four exemplar hotels were studied and 10 respondents responsible for hotel restaurants’ planning and operations were sampled in this multiple case study approach. A total of 13 challenges were identified, and thematic analysis found 10 common CSFs crucial to hotel restaurants. Among the 10 CSFs, 2 distinctive CSFs were identified playing exceptional roles, including: (1) the inseparable linkage between hotel restaurants and support centers, as well as (2) the inseparable linkage between hotel restaurants and revenue streams. Moreover, this study broadened the retrospective understanding of the term “inseparability” in service organizations, and also contributed several implications for hotel restaurant managers to incorporate into their businesses